Perlindungan Hukum Pemegang Sertifikat Hak Milik akibat Ketidaksesuaian Data Spasial dan Data Yuridis dalam Sistem Pendaftaran Tanah Elektronik - Satriani Satriani (Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to analyze the legal protection provided to Land Title Certificate (SHM) holders due to discrepancies between spatial and legal data in the electronic land registration system and to examine the responsibility of the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN) in ensuring the accuracy and validity of electronic land data. This study uses a normative legal method with a statutory, conceptual, and case-based approach. Legal materials were obtained through a literature review, including legislation, legal literature, scientific journals, and factual cases related to land data discrepancies in the Sentuh Tanahku application in Kendari City. The results indicate that legal protection for SHM holders is provided through preventive protection in the form of an accurate and integrated land administration system, as well as repressive protection through data correction mechanisms, mediation, and dispute resolution. Furthermore, ATR/BPN has the administrative and legal responsibility to verify, synchronize, update, and correct land data to ensure legal certainty of land rights. Therefore, accurate integration of spatial and legal data is a key requirement for realizing an electronic land registration system that can provide legal certainty and optimal protection for land rights holders.